Laboratory experiment on resilient modulus of BRA modified asphalt mixtures - Karami, M.; Nikraz, Hamid; Sebayang, S.; Irianti, L. (Chinese Society of Pavement Engineering, 2018)
The objective of this research is to determine the potential effect on the resilient modulus of asphalt mixtures of using granular Buton Rock Asphalt (BRA) modified binder. The indirect tensile stiffness modulus (ITSM) tests were performed to examine the resilient modulus of unmodified and BRA modified asphalt mixtures for dense graded aggregates of 10 mm (DG10) and 14 mm (DG14) based on standard AS-2891.13.1-1995. In these tests, three percentage of BRA natural binder, including 10%, 20% and 30% by total weight of asphalt binder, were chosen as a substitute for the base asphalt binder in the BRA modified asphalt mixtures, with the purpose of improving the resilient modulus values. According to the test results, the resilient modulus of BRA modified asphalt mixtures was higher as compared to the unmodified asphalt mixtures. A higher percentage of BRA modifier binder content resulted in a higher resilient modulus. Furthermore, the unmodified and BRA modified containing only 20% BRA modified binder of DG10 were tested under different conditions of temperature, rise time, and pulse period. The results indicated that the BRA modified asphalt mixtures containing 20% BRA modified binder were less sensitive to the changes in the temperature, traffic volume and loading frequency. In addition, the substitution of 20% BRA modifier binder reduced the effect of the rest period ratio and loading time on the resilient modulus of the asphalt mixtures.